The Effect of COVID-19 on a Short-Term Teacher-Education Program: The Israeli Case - Yael Fisher; Orna Shatz-Oppenheimer; Rinat Arviv Elyashiv (MDPI AG, 2024)
Given the unemployment wave caused by COVID-19, the Israeli Ministry of Education and other organizations initiated a unique alternative short-term retraining program to offer unemployed college and university graduates the opportunity to earn teaching certificates. This study aimed to examine the alternative short-term program from the coordinators' perspectives. We assess the personal and organizational impact of the program and its contribution to teacher-education initiatives. The present study had two main goals: to learn about the structure of the program and its implementation from the professional and personal points of view of the program's coordinators as they experienced it and to examine the contribution of the new short-term program to the participants-the teacher trainees-and the Israeli education system in general. Analyzing semi-structured interviews with program coordinators revealed insights regarding the program's various phases in five categories: recruitment of the coordinator; establishing the program; clinical experience; the students of the program; and future initiatives for teacher education. Although the effectiveness of the online format for practical clinical training was questioned, the conclusion suggests that this alternative short-term teacher-education program may have broader relevance in routine times.